Decision Making in a World of Comparative Effectiveness Research : A Practical Guide - Birnbaum, Howard G.; Greenberg, Paul E. (Springer Singapore : Imprint: Adis, 2017)
In the past decade there has been a worldwide evolution in evidence-based medicine that focuses on real-world Comparative Effectiveness Research (CER) to compare the effects of one medical treatment versus another in real world settings. While most of this burgeoning literature has focused on research findings, data and methods, Howard Birnbaum and Paul Greenberg (both of Analysis Group) have edited a book that provides a practical guide to decision making using the results of analysis and interpretation of CER. Decision Making in a World of Comparative Effectiveness contains chapters by senior industry executives, key opinion leaders, accomplished researchers, and leading attorneys involved in resolving disputes in the life sciences industry. The book is aimed at 'users' and 'decision makers' involved in the life sciences industry rather than those doing the actual research. This book appeals to those who commission CER within the life sciences industry (pharmaceutical, biologic, and device manufactures), government (both public and private payers), as well as decision makers of all levels, both in the US and globally.
Keywords: Medicine.; Pharmaceutical technology.; Pharmacy management.; Statistics.; Health economics.; Medical economics.; elektronické knihy; electronic books